Efficacy and Safety of Combination Treatment With Apatinib and Osimertinib After Osimertinib Resistance in Epidermal Growth Factor Receptor-Mutant Non-small Cell Lung Carcinoma—A Retrospective Analysis of a Multicenter Clinical Study - Yang, Xue; Xia, Yang; Xu, Liyan; Liang, Li; Zhuo, Minglei; Wu, Meina; An, Tongtong; Wang, Ziping; Wang, Yuyan; Li, Jianjie; Zhong, Jia; Chen, Hanxiao; et al. (Frontiers in Molecular Biosciences, 2021)
There are currently limited treatment options after resistance to osimertinib, a third-generation epidermal growth factor receptor (EGFR) inhibitor. Resistance to EGFR inhibitors is frequently associated with enhanced vascular endothelial growth factor (VEGF) levels. This study aimed to evaluate the efficacy of apatinib plus osimertinib after osimertinib resistance in EGFR-mutant non-small cell lung cancer (NSCLC) patients.This multicenter, retrospective study evaluated 39 EGFR-mutant NSCLC patients resistant to osimertinib. Patients received oral apatinib 250 mg qd plus osimertinib 80 mg qd. Efficacy was evaluated after the first month then every 2 months thereafter. The primary endpoint was progression-free-survival (PFS). The overall response rate (ORR) and disease control rate (DCR) of apatinib plus osimertinib was 12.8% (5/39) and 79.5% (31/39), respectively. The median PFS was 4.0 months (95% confidence interval [CI]: 3.5–4.5 months). Fourteen patients had received at least a 6-month combination therapy, 11 of whom were still on treatment. The 6-month PFS rate was 38%. Nine patients underwent biopsies after failing osimertinib treatment, and 5 of 6 patients with TP53 mutations had PFS less than 3 months. The spectrum of resistance mechanisms to osimertinib included c-met amplification, PIK3CA gain-of-function mutation, PTEN loss-of-function mutation, ERBB2 amplification, and IGF1R mutation. The most common adverse event was hypertension (30.7%, 12/39), diarrhea (15.4%, 6/39), and proteinuria (12.8%, 5/39). The combination of apatinib plus osimertinib in osimertinib-refractory EGFR-positive NSCLC improved the ORR and DCR, thus making it a reasonable treatment choice after osimertinib resistance.